FAKTOR – FAKTOR YANG MEMPENGARUHI PENGHIMPUNAN DEPOSITO MUDHARABAH PADA BANK PEMBIAYAAN RAKYAT SYARI’AH DI INDONESIA PERIODE 2015-2017 - ANGGARA DISUMA; Al Fitri Islami (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2019)
The Islamic community has now begun to have awareness of taking positive steps to abandon the usury that is in conventional banking and turn to islamic-based economic systems. One of the steps taken is to shift from conventional financial institutions to sharia financial institutions. This has a positive effect on the growth of Islamic banking, so that many conventional banks are turning to Islamic system into dual system. One of the products that can boost the growth of Islamic banking in Indonesia is deposits with the principle of mudaraba. The existence of mudaraba deposit products is stronger with the presence of the Indonesian Ulama Council's fatwa through the National Sharia Council (DSN) on Islamic deposits. However, in the fund raising of mudaroba deposits, the influence of internal institutional factors as well as macroeconomic factors can not be ignored.This study aims to determine how much influence the BI Rate, Profit Sharing, Inflation and Gold Price on the collection of Mudaroba Deposit at the BPRS in Indonesia period 2015-2017. This research moved from the hypothesis that there is the influence of interest rate (BI Rate), profit sharing, inflation and gold price partially or simultaneously (simultaneously) to the collection of mudaraba deposits. The research approach used is quantitative research approach with VAR (Vector Auto Regressive) analysis supported by stationar test, optimal lag test, VAR model stability test, granger causality test, impulse response function test and variance decomposition test, assisted by Eviews version 6 software. The sample used in this research is data of BI Rate, Profit Sharing, Inflation, Gold Price and Mudaraba Deposit from January 2015 until September 2017.The results of the study at 5% alpha, it can be concluded that the results of multiple regression analysis shows that the BI Rate variable, Profit Sharing, Inflation and Gold Price affect the collection of Mudaraba Deposits. In the short term or the initial period of Profit Sharing observations have the most dominant influence among other variables on the collection of Mudaraba deposits that is equal to 0.023% but the effect decreases until the end of the period. Whereas in the long run or the final period of observation Inflation has the most dominant influence on the collection of Muharaba Deposits compared to other variables that is equal to 1.06%. The BI Rate variable has an influence on the collection of Mudaraba Deposits by 0.712% and the Gold Price has an influence on the collection of Mudaraba Deposits by 0.78% at the end of the observation period. From the results of the classic assumption test shows that all variables have a causality relationship with each other, meaning that each variable has a 2-way relationship with other variables. While the results of statistical tests show that the collection of Mudaraba Deposits responds to the BI Rate variable is very balanced, responding to the Profit Sharing variable with a negative and increasingly balanced response, responding to the Inflation and Gold Price variables in a very balanced manner. Thus, it can be seen that the collection of Mudaraba Deposits in its development is more influenced by macroeconomic instruments by 1.06% compared to its own instruments, namely Profit Sharing by 0.023%. This means that the collection of Mudaraba Deposits in the banking sector, especially Islamic banking, is still influenced by the level of inflation. However, if it is reviewed again that Islamic banking cannot be separated from macroeconomic factors, one of which is inflation.